Tunable current duration in triboelectric generators via capacitive air gaps. (15th November 2020) - Seo, Byungseok; Cha, Youngsun; Kim, Sangtae; Choi, Wonjoon
Summary: Despite the low cost, high power, and wide application areas, impact‐type triboelectric generators exhibit limited applicability due to the extremely short current duration, on the order of a millisecond. The high power, short lasting current peak not only results in reduced time‐averaged power output but also acts as triboelectric shock to the accompanying circuits, quickly degrading the usability of the generator. Here, we demonstrate tunable triboelectric current duration via controlling the air gap capacitance inserted between the two dielectric plates. In typical contact‐type triboelectric generator with nylon/air gap/Polydimethylsiloxane (PDMS) multilayers, decreasing the vertical speed of the dielectric plates from 0.5 cm/s to 0.05 cm/s result in increased current duration from 0.10 second to 0.81 second. The increased peak duration accompanies decreased peak current, resulting in the optimal charge density of 0.163 nC/cm 2 at the vertical speed of 0.25 cm/s. Changing the air gap capacitance in noncontact mode or the relative permittivity in dielectric layers also results in similar change in peak duration. To explain the tunable current duration, an equivalent circuit model is constructed via serially connected capacitors and numerical solutions reproduce the trends in current duration associated with change in air gap capacitance. This study provides significant implications toward further optimizing triboelectric generators, in terms of optimal triboelectric charge density, accompanying circuit lifetime and broadened applicability. Abstract : We demonstrate tunable triboelectric current duration via controlling the air‐gap capacitance between two dielectric plates. In triboelectric generators with nylon/air‐gap/PDMS multilayers, decreasing the vertical speed of the dielectric plates (0.5 to 0.05 cm/s) results in an increased current duration (0.10 to 0.81 s), which accompanies decreased peak current, resulting in the optimal charge density (∼0.163 nC/cm 2 at the 0.25 cm/s). This study implies optimization of triboelectric generators in terms of optimal triboelectric charge density, accompanying circuit lifetime and broadened applicability.